2020
DOI: 10.1182/bloodadvances.2019000491
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies of multiple myeloma among men and women of African ancestry

Abstract: Persons of African ancestry (AA) have a twofold higher risk for multiple myeloma (MM) compared with persons of European ancestry (EA). Genome-wide association studies (GWASs) support a genetic contribution to MM etiology in individuals of EA. Little is known about genetic risk factors for MM in individuals of AA. We performed a meta-analysis of 2 GWASs of MM in 1813 cases and 8871 controls and conducted an admixture mapping scan to identify risk alleles. We fine-mapped the 23 known susceptibility loci to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Coding and regulatory variants of ELL2 have been associated with risk of multiple myeloma in European and African ancestry individuals as well as reduced levels of immunoglobulin A and G in healthy subjects. [53][54][55] Another set of genetic variants located $200 kb away in the promoter region of GLRX or glutaredoxin-1 (rs10067881 [chr5:95,826,771, GenBank: NC_000005.10, g.95826771G>A], rs17462893 [chr5:95, 827,733, GenBank: NC_000005.10, g.95827733A>G], rs57675369 [chr5:95,826,714, GenBank: NC_000005.10, g.95826714_95826715insG]) have been associated with (G) Indel frequency following 3xNLS-SpCas9:sgRNA targeting RUVBL1 coding sequence or neutral control locus in input cell 4 days after RNP electroporation or engrafted bone marrow samples 16 weeks after infusion to NBSGW mice. (H) Representative flow cytometry of human and mouse CD45 þ cells from NBSGW bone marrow 16 weeks after cell infusion (representative of 3 mice).…”
Section: Ell2mentioning
confidence: 99%
“…Coding and regulatory variants of ELL2 have been associated with risk of multiple myeloma in European and African ancestry individuals as well as reduced levels of immunoglobulin A and G in healthy subjects. [53][54][55] Another set of genetic variants located $200 kb away in the promoter region of GLRX or glutaredoxin-1 (rs10067881 [chr5:95,826,771, GenBank: NC_000005.10, g.95826771G>A], rs17462893 [chr5:95, 827,733, GenBank: NC_000005.10, g.95827733A>G], rs57675369 [chr5:95,826,714, GenBank: NC_000005.10, g.95826714_95826715insG]) have been associated with (G) Indel frequency following 3xNLS-SpCas9:sgRNA targeting RUVBL1 coding sequence or neutral control locus in input cell 4 days after RNP electroporation or engrafted bone marrow samples 16 weeks after infusion to NBSGW mice. (H) Representative flow cytometry of human and mouse CD45 þ cells from NBSGW bone marrow 16 weeks after cell infusion (representative of 3 mice).…”
Section: Ell2mentioning
confidence: 99%
“…Admixture mapping has also been used to refine PRS estimation, for example producing better discrimination in high risk percentiles for African Americans with multiple myeloma. 48 New methods for incorporating such findings into polygenic prediction algorithms are rapidly emerging, notably those incorporating both local and global ancestry adjustments. 49 , 50 , 51 Our findings similarly illustrate how observed risk distributions that differ across populations and as a function of the discovery ancestry group can be used to improve risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Costa et al [32] reported a 2.24-fold higher incidence of MM in AA men compared to CA men. Also, MM occurs in the AA population at an early age of 65.8 compared to age 69.8 in the CA population [33] . When considering polygenic risk scores (PRS), people of African ancestry in the top 10% PRS had a 1.82-fold (95%CI: 1.56-2.11) increased risk for MM compared to those with an average risk [34] .…”
Section: Genetic Predispositionmentioning
confidence: 92%